Directions of students of College of Primary Education of Sulaimani University about the use of artificial intelligence programs in the learning process - حمەلا, آ.م.د.رزگار; عارف, آ.م.د. کارزان محمد (Sulaimani Journal for Humanities, 2025)
This study seeks to explore and understand the attitudes of students at the College of Basic Education, University of Sulaymaniyah, towards the integration of artificial intelligence (AI) programs within the learning process. In alignment with the aims and nature of this inquiry, the researchers employed a descriptive survey methodology to systematically capture student perspectives. The study population comprised 2,408 students enrolled at the College of Basic Education during the 2024-2025 academic year, including 471 male and 1,937 female students. From this population, a random sample of 174 students was selected, consisting of 59 male and 115 female participants. To gather comprehensive and reliable data, the researchers designed a survey instrument consisting of 38 items organized into five thematic dimensions. This instrument was developed after a thorough review of relevant literature and prior studies. To ensure content validity, the survey was reviewed by a panel of experts specializing in teaching methods, psychology, and educational technology. Following their constructive feedback and minor revisions, the instrument received a high validation rate of 89 percent. Reliability was further established through a test-retest procedure, yielding a satisfactory reliability coefficient of 0.84. The finalized survey was administered electronically via Google Forms to the selected sample. Upon completion, the collected data underwent rigorous statistical analysis, with descriptive statistics including means, standard deviations, percentages, and item-level evaluations being calculated to elucidate the students’ attitudes. The results of the study showed that university students agree on the use and benefits of artificial intelligence tools in the learning and teaching process, as well as providing new opportunities for learning and improving the quality of learning and teaching. Based on the findings of this research, the study concludes with a series of practical recommendations and suggestions aimed at enhancing the effective implementation of AI tools in educational settings.
Keywords: Attitudes; University Students; Artificial Intelligence; Learning Process